Nutraceutical characterization of apricot fruits of the IVIA's collection - Gómez-Martínez, Helena; Bermejo, Almudena; Badenes, María L.; Zuriaga, Elena (ISHS, 2021)
Apricot (Prunus armeniaca L.) is an important stone fruit crop. The main production area is located in the Mediterranean basin countries, with Turkey, Italy, Greece, Spain and France included among the main world producers. Consumed as fresh or dried, in both cases apricots are excellent from the nutritional point of view. Their phenolics, vitamins and organic acids composition make this species interesting for human nutrition. Nowadays, there is a high consumer demand for nutraceutical type products. From the breeding point of view, in order to develop new apricot cultivars with improved fruit quality, it is mandatory to characterize the available materials as a starting point to enhance the program. At the IVIA's apricot breeding program, the fruit quality related to nutritional compounds is a relevant objective. In this study we analyzed the content of four phenolic compounds (neochlorogenic and chlorogenic acids, rutin and quercetin-3-glucuronide) in 23 genotypes from the IVIA's apricot collection. The collection showed a diverse nutraceutic profile. Goldrich cultivar presented the greatest amount of total phenolic compounds. However, the highest percentage of neochlorogenic and chlorogenic acids, corresponded to the hybrids GG9310 and GG937, respectively. On the other hand, the highest percentages of rutin and quercetin-3-glucuronide corresponded to the hybrid HG9869 and Orange Red cultivar, respectively. Moreover, the results revealed a positive correlation between pulp and peel contents. The results presented here pave the way to incorporate these traits into the future crosses of the IVIA's apricot breeding program.